PENGARUH BAURAN PEMASARAN DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN KONSUMEN MEMILIKI KARTU KREDIT BANK BRI DENGAN GAYA HIDUP SEBAGAI VARIABEL MODERATING - Mulfachriza, Mulfachriza; Bachri, Naufal; Biby, Sapna (Universitas Malikussaleh, 2021)
This study is aimed to identify the influence of marketing mix and service quality to customer’s decision to have BRI credit card with life style as a variable moderating. The samples of this study are 150 of kredit card’s holders at BRI Banda Aceh Regional Office. Structural Equation Modeling (SEM) with AMOS softaware was used to analyze the data. The results of the study indicate that marketing mix dan service quality has positive and significant influence on customer’s decision to have BRI credit card. Lifestyle could moderate each of marketing mix and service quality on customer’s decision to have BRI credit card.